Work–life balance/imbalance: the dominance of the middle class and the neglect of the working class1. (21st October 2015) - Warren, Tracey
Abstract: The paper was stimulated by the relative absence of the working class from work–life debates. The common conclusion from work–life studies is that work–life imbalance is largely a middle‐class problem. It is argued here that this classed assertion is a direct outcome of a particular and narrow interpretation of work–life imbalance in which time is seen to be the major cause of difficulty. Labour market time, and too much of it, dominates the conceptualization of work–life and its measurement too. This heavy focus on too much labour market time has rendered largely invisible from dominant work–life discourses the types of imbalance that are more likely to impact the working class. The paper's analysis of large UK data‐sets demonstrates a reduction in hours worked by working‐class men, more part‐time employment in working‐class occupations, and a substantial growth in levels of reported financial insecurity amongst the working classes after the 2008–9 recession. It shows too that economic‐based work–life imbalance is associated with lower levels of life satisfaction than is temporal imbalance. The paper concludes that the dominant conceptualization of work–life disregards the major work–life challenge experienced by the working class: economic precarity. The work–life balance debate needs to more fully incorporate economic‐based work–life imbalance if it is to better represent class inequalities.